PHARMACOGNOSTIC STUDIES OF ORGANICALLY CULTIVATED PANACEA HERB CYNODON DACTYLON (L.) PERS. - Lalit Raj Singh, (International Journal of Ayurveda and Pharma Research, 2019)
This research paper knuckles down the organic agripractices of the Cynodon dactylon (L.) Pers.. It is a powerhouse house of multiple macro and micro nutrients including protein, carbohydrates, carotenoids, flavonoids, phenolic compounds and vitamins. Organic cultivation practices enhances these secondary metabolites biosynthesis resulting in therapeutic potential of the crude drug. The field experimental work was conducted from Nov, 2018 up to Mar, 2019 in Department of Medicinal Plants Sciences at Dev Sanskriti Vishwavidyalaya, Haridwar (U.K), India. Cynodon herb belonging to Poaceae family was organically cultivated in our herbal field laboratory (no. 4) by planting slips line to line in experimental blocks. Physical parameters were studied including total Ash (9.9 % w/w), Acid-insoluble Ash (5.8 % w/w), Water-soluble Ash (2.4 % w/w), Alcohol soluble extractive (39.2 % w/w) and Water soluble extractive (39.8 % w/w). Based upon results, it is concluded that secondary metabolites are highly biosynthesized during organic agri practices. Cynodon is credited as panacea herb due to its vital therapeutic benefits in curing multiple acute and chronic diseases or disorders including erysipelas, depigmentation, hysteroepilepsy, Irritable bowel syndrome (IBS) and menstrual irregularities.